Education and state of autonomy in the face of the challenge of European multiculturalism - Esteve Zarazaga, José Manuel (Avances en Supervisión Educativa, 2005)
In this article, Dr. José Manuel Esteve presents the challenge for our country in a multinational political unit, as Europe hopes to be, as opposed to the variety of a state structured into Autonomous Communities.Through a review of our history, since the reign of the Catholic Monarchs to the present day, he describes specific moments in which the administration has tried to unify by law the variety of Spain, carrying out what he calls a "melting-pot policy".According to him, the process of European unification should stand upon the reinforcement of a common body of values which are able to promote a European identity and boost real unity through variety.The present day situation, which transfers to the educational field the different ways of socialization produced by a multicultural and multilingual society, contemplates new educational problems, among them the qualification of teachers to teach in a class that comprises students from different origin, the supervision and enlargement of curricular contents and the learning languages in order to improve communication between peoples.In short, he supports a multifaceted outlook on education after the acceptance of variety.